The private life of medicine: accounting for antibiotics in the 'for-profit' hospital setting. Issue 4 (November 2018) - Broom, Alex; Gibson, Alexandra; Kirby, Emma; Davis, Mark; Broom, Jennifer
Abstract The looming global antibiotic crisis, and the need to curtail over-use, has been positioned variously as a medical problem, an urgent public health concern, and an issue of governance and political will. But few questions have been raised in terms of its economic drivers. Specifically, how infection management—and the problematic of antimicrobial resistance—may be deeply embedded in economic imperatives and relations of labour. Drawing on interviews with 31 health professionals (doctors, nurses, pharmacists) from a private hospital in Australia, we explore their accounts of the dynamics of care and the economic imperatives in (and beyond) infection management. We argue that market-driven forces create a distinct set of obligations that could undermine the local and global antibiotic optimisation agenda. Given the increasingly privatised landscape of healthcare in Australia and internationally, exploring the nexus of economics and practice will be vital in retaining antibiotics for the future.